2019
DOI: 10.1109/access.2019.2891786
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Uncertainties on Resilient Operation of Microgrids: A Data-Driven Approach

Abstract: In this paper, the impact of uncertainties in loads, renewable generation, market price signals, and event occurrence time on the feasible islanding and survivability of microgrids is analyzed. A data-driven approach is proposed for estimating the maximum deviation level of uncertain parameters dynamically based on historical data. Similarly, fragility curves are utilized for determining the preparation time for the potential events based on the estimated event occurrence time and physical constraints of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…A resilience metric based on the speed of the system response, efficiency of the recovery, and economy of the recovery has been proposed in [48] to quantify system resilience after extreme events. In [49], [50], a resilience metric has been defined as the ratio of recovered loads to the actual loads of AC/DC sides of microgrids. This metric ensures the survivability of at least the most critical loads [49], [50].…”
Section: B Metrics Based On Resilience Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A resilience metric based on the speed of the system response, efficiency of the recovery, and economy of the recovery has been proposed in [48] to quantify system resilience after extreme events. In [49], [50], a resilience metric has been defined as the ratio of recovered loads to the actual loads of AC/DC sides of microgrids. This metric ensures the survivability of at least the most critical loads [49], [50].…”
Section: B Metrics Based On Resilience Featuresmentioning
confidence: 99%
“…In [49], [50], a resilience metric has been defined as the ratio of recovered loads to the actual loads of AC/DC sides of microgrids. This metric ensures the survivability of at least the most critical loads [49], [50]. Also, it is measured on a scale from zero to one where zero represents the lowest resilient level and one represents the highest level [49], [50].…”
Section: B Metrics Based On Resilience Featuresmentioning
confidence: 99%
“…However, there is only limited research focusing on the development of resilience-driven operational strategies for AC/DC MGs or DC MGs. In [20]- [22], both feasible islanding and the survivability of critical loads are considered to enhances the resilience of a hybrid MG. Based on above research, a datadriven method is suggested in [23] to estimate the impact of dynamic uncertain bounds on the resilient operation of hybrid MGs and a demand response program is considered to reduce load shedding during emergency period. In [24], a resiliencedriven robust dispatching model is developed to obtain the robust plans in the worst scenario for a hybrid MG with the consideration of uncertain event occurrence time.…”
Section: Ac(dc) Side Variables ∆Ementioning
confidence: 99%
“…In [30], a preparedness index is developed to calculate the total storage of electrical and thermal before the event onset, which is used to assess the resilience of a distribution system in pre-disturbance phase. In [10], [23], a resilience index is proposed to assess the survivability of loads with different priorities. Similarly, a resilience metric is proposed in [31]- [33] to evaluate the contribution of a optimal strategy on critical load restoration during the restorative phase.…”
Section: B Existing Research On Resilience Assessmentmentioning
confidence: 99%
See 1 more Smart Citation